Profile of Chemical Teacher Candidates High Order Thinking Skills (HOTS) on Ionic EquilibriumTopic - Rasmiwetti, Rasmiwetti; Abdullah, Abdullah; Ardiansyah, Ardiansyah (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research aims to (1) develop valid problems to measure Higher Order Thinking Skills (HOTS) for chemical teacher candidates on ionic equilibrium topic (2) evaluate chemical teacher candidatesâ HOTS on ionic equilibrium topic. Research is a development research type formative research that consist of analyzing, designing, evaluating, and revising. All data are analyzed using descriptive technique. Subject in this research are chemical teacher candidates of University of Riau Chemical Education Study Program. The results of this research are: (1) four of valid HOTS problems on ionic equilibrium topic. (2) value of chemical teacher candidatesâ HOTS on ionic equilibrium topic is 33.18 which put in medium category.